THE INFLUENCE OF HUMAN RESOURCE MANAGEMENT ON SERVICE QUALITY AT THE VILLAGE ADMINISTRATION OFFICE - Mahyudin Situmeang (Universitas Negeri Medan, 2022)
The research problem is how much influence Human Resource Management has on the Service Quality of the Sei Rotan Village Office, Percut Sei Tuan District, Deli Serdang Regency,Human Resource Management is measured in dimensions Planning (planning), Organizing (organizing), Directing (directing), Supervision (controlling).to (Y) Service Quality in Tangibles dimension, (physical factor) Reliable (true), Responsiveness (responsiveness), Assurance (Guarantee)and Empathy (Caring) The research method uses an explanatory survey method. Data collection techniques using a closed questionnaire with a Likert scale model and interviews. The population and sample of the study were 47 people. Data analysis is Path Analysis Models (Part Analysys Models) with statistical test t-test and F-test with the help of SPSS 21.0 for Windows. The results of research on the influence of Human Resource Management (X) in the dimensions ofPlanning (planning), Organizing (organizing), Directing (directing), Supervision (controlling) to (Y) Service Quality In Tangibles dimension, (physical factor) Reliable (true), Responsiveness (responsiveness), (Assurance)and Empathy (Caring)is a low effect of 37.25%. Service Quality in Tangibles dimension, (physical factor) Reliable (true), Responsiveness (responsiveness), Assurance (Guarantee)and Empathy (Caring)is small 35.39% low category. Influence of Human Resource Management (X) in dimensionPlanning (planning), Organizing (organizing), Directing (directing), Supervision (controlling).